Castleman's Disease: A Case Report of the Unicentric Type. (10th September 2012) - Gomez-Ramirez, J.; Posada, M.; Sanchez-Urdazpal, L.; Martin-Perez, E.; Del Campo, L.; Garcia, I.; Martin, J. L.; Larrañaga, E.
Abstract : Castleman's disease, or angiofollicular lymph node hyperplasia, is a relatively rare disorder characterized by the benign proliferation of lymphoid tissue related to the chronic human herpes virus 8 (HHV-8) infection and the human immunodeficiency virus (HIV). Two clinical entities have been described: a unicentric presentation with the disease confined to a single anatomic lymph node and a multicentric presentation characterized by generalized lymphadenopathy and a more aggressive clinical course. Also, three histopathological subtypes have been described: hyaline-vascular, plasma cell, and a mixed variant. Preoperative diagnosis of hyaline-vascular Castleman's disease is difficult, and the definitive result is based on postoperative pathological findings. The gold standard therapy is the complete surgical excision.